Hybrid Lump-Element Microstrip Filters - Ho, Yi Sing (2012)
In this thesis lump-element method for miniaturisation of microstrip patch without degrading its radiation characteristics is investigated. It involves replacing lumped element to form microstrip coupled line filters, microstrip power dividers and microstrip rings which are investigated numerically and experimentally. Filters are usually used to let the selected frequencies to pass and reject other unwanted frequencies through the devices. Power dividers are used to couple electromagnetic signal from a transmission line to another. There are three major stages in this project: simulation, fabrication and experiment. Ansoft High Frequency Structure Simulator (HFSS) version 8 software has been used in this project in order to simulate the BPF performance for different configurations. With the help of a software, the width of the 50ohm transmission line is calculated. Advanced Wiring Revolution Design Environment (AWR) software is also used to model the proposed configurations of my project. The results are compared with those generated by the HFSS software. Experiment will be conducted to verify the simulation and measured by using the Vector Network Analyzer (VNA) in the laboratory. The computed results are compared with experimental data and again good agreement is obtained. Several case studies have been done on the proposed configuration in order to study the relationship between different values of lump-elements. The proposed project designs should be useful for reduce size in designing filter, power divider and ring.